2004
DOI: 10.1161/01.cir.0000118465.36018.2d
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Endothelial Locus-1 (Del-1), a Novel Angiogenic Protein

Abstract: Background-Developmentally regulated endothelial locus-1 (Del-1) is an extracellular matrix protein that is expressed by endothelial cells during embryological vascular development. We speculated that Del-1 may be reexpressed in ischemia and may be involved in endogenous angiogenesis. Methods and Results-Del-1 protein was detected by immunohistochemistry in murine ischemic hindlimb after femoral artery excision. To determine whether exogenous Del-1 would augment angiogenesis in vivo, Del-1 or vehicle was admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 22 publications
2
53
0
3
Order By: Relevance
“…L'activation des intégrines, même en l'absence de facteurs de croissance, peut affecter l'angiogenèse. Cela a notamment été démontré pour Del-1, l'analogue de la lactadhérine [3,4]. De même, nos travaux prouvent que la lactadhérine interagit avec les intégrines αvβ3 et αvβ5 et, par un mécanisme dépendant d'AKT, qu'elle est capable d'activer le développe-ment de nouveaux vaisseaux dans un contexte ischémique en l'absence de VEGF exogène ( Figure 2D).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…L'activation des intégrines, même en l'absence de facteurs de croissance, peut affecter l'angiogenèse. Cela a notamment été démontré pour Del-1, l'analogue de la lactadhérine [3,4]. De même, nos travaux prouvent que la lactadhérine interagit avec les intégrines αvβ3 et αvβ5 et, par un mécanisme dépendant d'AKT, qu'elle est capable d'activer le développe-ment de nouveaux vaisseaux dans un contexte ischémique en l'absence de VEGF exogène ( Figure 2D).…”
Section: Discussionunclassified
“…La physiopathologie de l'infection reste mal comprise. La porte d'entrée est probablement respiratoire, aboutissant à une primo-infection pulmonaire souvent asymptomatique, puis la levure persisterait dans l'organisme sous une forme latente [3]. À la faveur d'une immunosuppression, la levure serait…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Hypoxia was shown to increase Del1 expression in endothelial cells (Scheurer et al, 2004). Thus, Del1 acts as an angiogenic factor to stimulate vascularization (Penta et al, 1999;Ho et al, 2004). It has been suggested that Del1 may also have a role in the angiogenic remodeling of vascular tissue after ischemic damage (Ho et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Del1 acts as an angiogenic factor to stimulate vascularization (Penta et al, 1999;Ho et al, 2004). It has been suggested that Del1 may also have a role in the angiogenic remodeling of vascular tissue after ischemic damage (Ho et al, 2004). Del1 promotes solid tumor expansion by inducing endothelial cell formation, which leads to the suppression of tumor apoptosis by increasing blood flow supply (Aoka et al, 2002).…”
Section: Introductionmentioning
confidence: 99%